Pushing One's Luck: Petroleum Ownership and Discoveries - Christa N. Brunnschweiler; Steven Poelhekke (Center for Economic Studies and ifo Institute (CESifo), 2021)
We present a new dataset that tracks changes in legal ownership regimes in the petroleum sector between 1867 and 2008 for a panel of countries. We document that foreign ownership has been taken over by partnerships as the leading ownership regime, while domestic ownership is on the rise again in recent years. We use this dataset to examine whether institutional change in the petroleum sector leads to more oil and gas exploration and discoveries. On average, switching to majority foreign ownership is related to up to a quarter of a standard deviation more discoveries than under majority domestic ownership. Switching to partnership is positively related to drilling activity, but is less likely to be linked to many more discoveries. Petroleum exploration and discoveries may thus be endogenous to industry-specific institutional change.
Keywords: E02; O43; Q30; 330; discoveries; oil and gas; natural resources; institutions